Pro SQL Server 2005 Service Broker - Aschebrenner, Klaus; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
Provides information on writing message-based applications using the Server Broker feature of SQL Server 2005.
Includes index.
Keywords: Microsoft SQL server 2005.; Client/server computing; Database management; Computer Science; Programming Techniques